Can Pro-Marriage Policies Work? An Analysis of Marginal Marriages - Wolfgang Frimmel; Martin Halla; Rudolf Winter-Ebmer (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2012)
Policies to promote marriage are controversial, and it is unclear whether they are successful. To analyze such policies, it is essential to distinguish between a marriage that is created by a marriage-promoting policy (marginal marriage) and a marriage that would have been formed even in the absence of a state interven- tion (average marriage). In this paper, we exploit the suspension of a cash-on-hand marriage subsidy in Austria to examine the differential behavior of marginal and average marriages. The announcement of this suspension led to an enormous marriage boom (plus 350 percent) among eligible couples that allows us to identify marginal marriages. Applying a difference-in-differences approach, we show that marginal marriages are surprisingly as stable as average marriages, but have fewer children and have them later in marriage. Notably, the children born to marginal marriages are similar in terms of health at birth.
Keywords: J12; H24; H53; I38; 330; Marriage-promoting policies; marriage subsidies; marital instability; divorce; fertility